FARMER-HERDER CONFLICTS IN DELTA STATE, NIGERIA – A SOCIO-ENVIRONMENTAL STUDY - Idisi, Benjamin; Vremudia, Wekpe; Ogbereyivwe, Oghovese (FUDMA Journal of Sciences, 2026)
Farmer-herder conflicts have intensified across Nigeria in recent years, threatening agricultural productivity, food security, and community development, especially in southern regions such as Delta State. Driven by competition over land, water, and grazing resources amid climate change and population growth, these clashes have received limited scholarly attention in the Niger Delta compared to northern and middle-belt areas. This study investigates the socio-economic, infrastructural, and developmental impacts of farmer-herder conflicts on rural communities in Delta State, Nigeria. A mixed-methods approach combined quantitative surveys (N = 400) with qualitative focus group discussions (FGDs; n = 12) and key informant interviews (KIIs; n = 15) across four local government areas: Ughelli North, Ethiope East, Ukwuani, and Ndokwa West. Stratified random sampling ensured demographic representation. Quantitative data were analyzed using SPSS (descriptive/inferential statistics, including chi-square tests and binary logistic regression), while qualitative data underwent thematic analysis in NVivo. Findings show that 68.5% of respondents experienced conflicts in the past five years, mainly triggered by crop destruction (78.0%), unauthorized grazing (65.5%), land encroachment (51.3%), and livestock theft (34.8%). Consequences included reduced agricultural yields (72.1%), income losses (68.0%), food insecurity, displacement, eroded social cohesion (64.7%), and ineffective institutional responses (only 18.0% rated effective). Women suffered disproportionate effects, such as livelihood disruption and violence. Inferential analyses confirmed significant links between conflict exposure and income loss/displacement (p < 0.05), with unauthorized grazing and land encroachment predicting food insecurity.
Keywords: Farmer-Herder Conflicts; Community Development; Conflict Resolution; Rural Livelihoods; Agro-Pastoralism; Nigeria